2018
DOI: 10.5194/acp-2018-753
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aerosol hygroscopic growth, contributing factors and impact on haze events in a severely polluted region in northern China

Abstract: Abstract:1 The hygroscopic growth of aerosol particles is a key factor of air pollution because it 2 can significantly reduce visibility. In order to better understand the impact of the 3 hygroscopic growth effect on haze events and contributing factors, we made use of rich 4 measurements during an intensive field campaign conducted in Xingtai, Hebei province 5 of China that has suffered from the most serious pollution in the Northern China Plain. 6Key measurements are from Raman lidar and ground-based instrum… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 37 publications
(56 reference statements)
2
12
0
Order By: Relevance
“…For CHARMS, the median retrieved κ ext ( γ ) was 0.31 (0.66) and 0.27 (0.61) for 355 and 532 nm, respectively (Figures 1a and 1b). Values retrieved for γ are similar to those from the recent study by Chen et al (2019). Interestingly, the composition from the ACSM during CHARMS (see supporting information) indicated a likely presence of weak organic acids as compared to the more acidic aerosol in Chen et al (2019).…”
Section: Resultssupporting
confidence: 88%
“…For CHARMS, the median retrieved κ ext ( γ ) was 0.31 (0.66) and 0.27 (0.61) for 355 and 532 nm, respectively (Figures 1a and 1b). Values retrieved for γ are similar to those from the recent study by Chen et al (2019). Interestingly, the composition from the ACSM during CHARMS (see supporting information) indicated a likely presence of weak organic acids as compared to the more acidic aerosol in Chen et al (2019).…”
Section: Resultssupporting
confidence: 88%
“…Comparatively, measurements made at Xingtai, one of the most polluted regions in China, showed that aerosol particles are more hydrophilic and thus have a stronger swelling effect associated with the internal mixing of secondary aerosol species (Wang et al, ). By combining aerosol chemical composition measurements, Chen et al () further analyzed the roles of different aerosol species in affecting aerosol hygroscopic growth in Xingtai. However, most measurements of hygroscopicity are currently limited to the ground level.…”
Section: Aerosol Formation Nucleation Optical Properties and Radiamentioning
confidence: 99%
“…Average aerosol hygroscopicity, especially for the more hygroscopic mode, usually increased with pollution levels (Massling et al, 2009;Wu et al, 2016;Y. Wang et al, 2017b;Chen et al, 2019;Ding et al, 2019;, which is attributed to increased mass fractions of secondary inorganic aerosols. However, different results were also reported, especially for particles at or below 50 nm (Achtert et al, 2009;Meier et al, 2009; for which primary emissions could play an important role.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al, 2018a), aerosol hygroscopicity on a clean day (21 May) was compared with that on a highly polluted day (23 May). Aerosol hygroscopicity was higher on the polluted day (Chen et al, 2019), likely due to the enhanced formation of nitrate as revealed by aerosol chemical speciation monitor (ACSM) measurements. Furthermore, aerosol hygroscopicity increased with particle size (40-200 nm) on both days, with average κ values increasing from 0.288 to 0.339 on 21 May and from 0.325 to 0.352 on 23 May (Chen et al, 2019).…”
Section: Hebei Provincementioning
confidence: 99%